THE QUR’AN’S WISDOM ON “THE OTHER CULTURES” - Ridwan, Nur Khalik (Universitas Islam Indonesia, 2019)
This paper seeks to discuss how the Qur’an deal with the question of cultural differences and diversity. It argues that although the Qur’an and Islam both originated from the Arabic culture (maddatul Arab), it does not mean the holy book does not allow “other” cultures and traditions. Instead, it contains values beyond Arabic materials. This means Islam recognizes the diversity of cultures and traditions in society. Moreover, Islam expresses its universal values by exposingits wisdom in dealing with cultural differences and diversity.